2017
DOI: 10.12681/bgsg.11333
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Bayesian Approach in Gis Based Model for Evaluating Landslide Susceptibility. Case Study Kimi Area, Euboea, Greece

Abstract: The purpose of this study is to present a Bayesian approach (weight-of-evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
0
13
0
8
Order By: Relevance
“…The technique was later extended to determining animal habitats, archaeology, environmental impact evaluation, risk assessment and also used in wildfire prediction (Dickson et al, 2006;Ford, Clarke, & Raines, 2009;Ilia, Tsangaratos, Koumantakis, & Rozos, 2017;Lv, Zheng, Zhao, & Hu, 2013;Raines & Bonham-Carter, 2007;Romero-Calcerrada, Novillo, Millington, & Gomez-Jimenez, 2008, 2010Tahmassebipoor, Rahmati, Noormohamadi, & Lee, 2016;Weed, 2005). The method assumes that an event occurs at a set of known presence points and uses evidence from multiple evidential themes that might cause the event expressed in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique was later extended to determining animal habitats, archaeology, environmental impact evaluation, risk assessment and also used in wildfire prediction (Dickson et al, 2006;Ford, Clarke, & Raines, 2009;Ilia, Tsangaratos, Koumantakis, & Rozos, 2017;Lv, Zheng, Zhao, & Hu, 2013;Raines & Bonham-Carter, 2007;Romero-Calcerrada, Novillo, Millington, & Gomez-Jimenez, 2008, 2010Tahmassebipoor, Rahmati, Noormohamadi, & Lee, 2016;Weed, 2005). The method assumes that an event occurs at a set of known presence points and uses evidence from multiple evidential themes that might cause the event expressed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A negative contrast means a negative correlation (the factor reduces wildfire ignition), and conversely, a positive contrast represents a positive relation or direct causation (Corsini, Cervi, & Ronchetti, 2009;Tahmassebipoor et al, 2016). Since C usually shows uncertainty (Bonham-Carter, 1994), C S , the Studentized value of C, is more often used than C in the selection of evidence variables and in the breakpoints in their classes (Ilia et al, 2017;Romero-Calcerrada et al, 2010). Given n evidence factors, the potential distribution of probability for every spatial cell, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The performed sensitivity analysis was found to be significant for the validation and calibration of developed model. The effectiveness of the proposed approach has been evaluated in the municipality of Kimi, an area experienced with substantial landslide events, as reported in previous studies (Ilia et al , 2010Ilia 2013). The present study used detail data with a total number of 132 landslide events recorded in the period of 2008-2012 by applying the WofE method with eight variables which were converted into a 5×5 m 2 grid cell.…”
Section: Introductionmentioning
confidence: 99%
“…As can be reviewed through the scientific literature, numerous studies can be found that utilize bivariate statistics (Thiery et al 2007;Magliulo et al 2008;Yilmaz et al 2012), multivariate methods that implement discriminant analysis (Lee et al 2008) or linear and logistic regression (Dai and Lee 2003;Ayalew and Yamagishi 2005;Duman et al 2006;Chauhan et al 2010;Akgun 2012), frequency ratio (Lee and Sambath 2006;Pradhan 2006, 2007;Yilmaz 2010;Akinci et al 2011), certainty factor approach (Binaghi et al 1998;Lan et al 2004;Sujatha et al 2012), Dempster-Shafer, and weight of evidence models (Lee et al 2004a;Tangestani 2009;Cervi et al 2010;Ilia et al 2010;Park 2010;Armas Landslides Original Paper 2012;Neuhauser et al 2012;Tien Bui et al 2012a;Thiery et al 2014). In addition to these methodological approaches, new methods and techniques have been applied for landslide susceptibility, hazard, and risk evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation